Oblongolides from the endophytic fungus Phomopsis sp. BCC 9789 - Taridaporn Bunyapaiboonsri (2018)
Six new oblongolides, W1, W2, X, Y, and Z (1-3, 6, 7) and 2-deoxy-4α-hydroxyoblongolide X (4), and the known compounds oblongolide (8), oblongolides T, C, and Q (5, 9, 10), and (-)-5-methylmellein were isolated from the endophytic fungus Phomopsis sp. BCC 9789. Compound 7 showed anti-HSV-1 activity (IC50 ) 14 μM) and cytotoxic activities against KB, BC, NCI-H187, and nonmalignant (Vero) cell lines with respective IC50 values of 37, 26, 32, and 60 μM. Cytotoxic activity against the BC cell line was also observed for compound 6, with an IC50 value of 48 μM. © 2010 American Chemical Society and American Society of Pharmacognosy.